Concrete water-retention anti-cracking internal curing agent and preparation method thereof
The concrete water-retaining and crack-resistant internal curing agent is produced through the synthesis-composite method, and the polyacrylic acid-acrylamide cross-linked products and hydrated calcium silicate and other materials are used to solve the problems of high cost and poor effect of existing spray curing agents, and the effect of significantly improving the water-retaining and crack-resistant properties of concrete at low dosages is achieved.
Patent Information
- Application Number
- CN202510417452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-06-17
AI Technical Summary
The existing concrete spray curing agent has high cost and poor water conservation and crack resistance in environments with large temperature difference and humidity changes. In the construction of concrete with complex structures, the problem of incomplete spray curing is prone to occur.
The synthetic-complex method is used to produce concrete water-retaining and crack-resistant internal curing agent. By synthesizing polyacrylic acid-acrylamide cross-linked product and hydrated calcium silicate, combining calcium sulfate whiskers and sodium carbonate as self-contact reinforcement components, nano-scale hydrated calcium silicate is formed to improve the water-retaining and crack-resistant properties of concrete.
At a low internal dosage, the water retention and crack resistance of concrete is significantly improved, ensuring that concrete still has excellent crack resistance under conditions of large temperature difference and humidity changes, and is non-toxic and harmless, making it more energy-saving and environmentally friendly.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete admixtures, and particularly relates to a concrete water-retaining and crack-resistant internal curing agent and a preparation method thereof. Background Art
[0002] Concrete curing is an important process in the development of concrete durability and strength. Especially in the concrete construction operations in high-temperature difference and high-altitude areas, improper concrete curing will lead to incomplete hydration due to water loss in the concrete, resulting in problems such as cracking and shrinkage, which affect the durability and strength of the concrete.
[0003] At present, the anti-cracking curing of concrete in high-temperature difference and high-altitude areas is mainly carried out by spraying curing agents. However, the cost of concrete spraying curing agents is high and they are greatly affected by the environment. Under the conditions of large temperature difference and humidity changes, the water-retaining curing and anti-cracking effects are poor, and in the concrete construction with complex structures, it is easy to have the phenomenon of incomplete spraying curing and poor local curing.
[0004] At present, the internal admixture type concrete water-retaining curing and anti-cracking agent is a new trend in engineering construction curing. However, the existing internal admixture curing agents in China have a high dosage and high cost, and the curing effect is poor in the working environment with large temperature difference and humidity, resulting in the internal admixture curing agent being in its infancy in actual engineering applications. The market needs an internal admixture concrete water-retaining and crack-resistant internal curing agent with high adaptability for project curing in complex areas. Summary of the Invention
[0005] To solve the above technical problems, the present invention provides a concrete water-retaining and crack-resistant internal curing agent and a preparation method thereof. The concrete water-retaining and crack-resistant agent is produced by a synthesis-compounding method, which can exert good concrete curing functions at a low internal admixture dosage, improve the water-retaining and crack-resistant properties of the concrete, and ensure that the concrete still has excellent crack-resistant properties under the conditions of large temperature difference and humidity changes; the preparation method is non-toxic and harmless, and is more energy-saving and environmentally friendly.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The present invention provides a concrete water-retaining and crack-resistant internal curing agent, which is prepared from the following raw materials in parts by weight: 22-37 parts of sodium metasilicate, 26-37 parts of calcium nitrate tetrahydrate, 30-47 parts of polyacrylic acid, 22-35 parts of acrylamide, 11-22 parts of N,N-methylenebisacrylamide, 21-30 parts of calcium sulfate whiskers, 14-22 parts of sodium carbonate, 7-18 parts of hydroxypropyl cellulose ether, 0.4-1.4 parts of reducing agent, 3-5 parts of oxidizing agent, 1.2-2 parts of chain transfer agent, and 550-900 parts of deionized water.
[0008] The molecular weight of the polyacrylic acid is 1,000 - 3,000. The viscosity of the internal curing agent for concrete water retention and crack resistance prepared from polyacrylic acid within this molecular weight range is appropriate. If the molecular weight is too large, the viscosity of the curing agent will be relatively high and the dispersibility will be poor.
[0009] The particle size of the calcium sulfate whiskers is 300 - 600 mesh, and the solubility and dispersibility of the calcium sulfate whiskers with such a particle size are better.
[0010] The reducing agent is ascorbic acid and Rongalite.
[0011] The oxidizing agent is hydrogen peroxide or ammonium persulfate.
[0012] The chain transfer agent is 3 - mercaptopropionic acid, mercaptoacetic acid or mercaptoethanol.
[0013] The present invention also provides a preparation method of the internal curing agent for concrete water retention and crack resistance, and the preparation method includes the following steps:
[0014] S1: First, stir and mix the formula amount of polyacrylic acid, part of acrylamide and part of deionized water;
[0015] S2: Add the formula amount of oxidizing agent to the mixed solution obtained in step S1, stir evenly, and then simultaneously dropwise add material A composed of N,N - methylene bisacrylamide and the remaining part of acrylamide and part of deionized water, and material B composed of reducing agent and chain transfer agent. After the dropping is completed, stir and keep warm. After the heat preservation ends, a polyacrylic acid - acrylamide cross - linked product A is obtained;
[0016] S3: Mix the polyacrylic acid - acrylamide cross - linked product A obtained in S2 with part of deionized water, stir and heat up to 40 - 42 °C. While maintaining the temperature, simultaneously dropwise add calcium nitrate tetrahydrate solution and sodium metasilicate solution. After the dropping is completed, perform shear stirring and heat preservation, and then cool to room temperature and add hydroxypropyl cellulose ether, and stir to obtain reaction product B;
[0017] S4: Add the remaining deionized water to reaction product B, dilute to a solid content of 20 - 40%, add sodium metasilicate, sodium carbonate and calcium sulfate whiskers, and perform shear stirring and mixing evenly to obtain the internal curing agent for concrete water retention and crack resistance.
[0018] The mass ratio of acrylamide used in step S1 to acrylamide in material A is 1:3 - 10.
[0019] In step S2, the dropping time of material A is 60 - 100 min, and the dropping time of material B is 80 - 120 min.
[0020] In step S2, the time of shear stirring and heat preservation is 1 ± 0.5 h, and the temperature is 15 - 20 °C
[0021] In step S3, the dropping time of the calcium nitrate tetrahydrate solution and the sodium metasilicate solution is 50 to 80 min; the stirring and heat preservation time is 2.5 to 3.5 h.
[0022] In step S3, the mass concentration of the calcium nitrate tetrahydrate solution is 50 to 70%; the mass concentration of the sodium metasilicate solution is 5 to 15%.
[0023] In step S3, the stirring is shear stirring at a rotation speed of 500 - 600 r / min.
[0024] In step S4, the rotation speed of the shear stirring is 500 - 600 r / min.
[0025] The present invention also provides a kind of concrete, and the concrete water retention and crack resistance internal curing agent described in the present invention is used in the concrete.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The present invention uses a step - by - step method to synthesize the concrete water retention and crack resistance internal curing agent. In the first step, a polyacrylic acid - acrylamide cross - linked product with water retention function is synthesized, which can not only release the adsorbed water molecules during the hydration of concrete to promote hydration and prevent cracking, but also serve as a suspension stabilizing component of the self - compacting and strengthening component in the second step to improve the stability of the system.
[0028] 2. The present invention uses calcium nitrate and sodium metasilicate to synthesize nanoscale calcium silicate hydrate through heating and high - speed shearing, and compound sodium sulfate whiskers and sodium carbonate as self - compacting and strengthening components, which can improve the strength development of concrete during the curing process, and can maintain suspension stability in the polyacrylic acid - acrylamide polymer and hydroxypropyl cellulose ether alkaline aqueous solution system, so that the concrete water retention and crack resistance internal curing agent can be stored stably for a long time.
[0029] 3. The concrete water retention and crack resistance internal curing agent provided by the present invention is non - toxic and harmless. Compared with traditional inorganic salt - based internal curing agents, it has a lower dosage, better curing effect, higher cost performance, and is more environmentally friendly. Detailed implementation mode
[0030] The present invention will be described in detail below in conjunction with the embodiments.
[0031] Example 1
[0032] A kind of concrete water retention and crack resistance internal curing agent is prepared from the following raw materials in parts by weight: 22 parts of sodium metasilicate, 36 parts of calcium nitrate tetrahydrate, 37 parts of polyacrylic acid with a molecular weight of 1000, 26 parts of acrylamide, 11 parts of N,N - methylene bisacrylamide, 25 parts of 300 - mesh calcium sulfate whiskers, 15 parts of sodium carbonate, 12 parts of hydroxypropyl cellulose ether, 0.7 part of ascorbic acid, 4 parts of hydrogen peroxide, 1.2 parts of 3 - mercaptopropionic acid, and 550 parts of deionized water.
[0033] The preparation method of the concrete water-retaining and crack-resistant internal curing agent includes the following steps:
[0034] S1: Add 37 parts of polyacrylic acid and 5 parts of acrylamide into a four-necked flask, add 200 parts of deionized water, and stir evenly at 20°C;
[0035] S2: Add 4 parts of hydrogen peroxide to the four-necked flask in step S1. After stirring evenly, simultaneously dropwise add material A composed of 11 parts of N,N-methylenebisacrylamide, 21 parts of acrylamide and 100 parts of deionized water, and material B composed of 0.7 part of ascorbic acid and 1.2 parts of 3-mercaptopropionic acid. The dropping time of material A is 80 min, and the dropping time of material B is 100 min. After the dropping is completed, stir and keep warm at 20°C for 1 h to obtain polyacrylic acid-acrylamide cross-linked product A.
[0036] S3: Add 200 parts of deionized water to the polyacrylic acid-acrylamide cross-linked product A obtained in step S2, shear and stir at 600 r / min to raise the temperature to 40°C. Under the condition of heat preservation, simultaneously dropwise add a 60% mass concentration calcium nitrate tetrahydrate solution containing 36 parts of calcium nitrate tetrahydrate and a 10% mass concentration sodium metasilicate solution containing 12 parts of sodium metasilicate. The dropping time is 1 h, and the heat preservation time is 3 h; after cooling to room temperature, add 12 parts of hydroxypropyl cellulose ether and stir to obtain reaction product B;
[0037] S4: Add the remaining parts of deionized water to dilute the reaction product B obtained in step S3, and add 25 parts of calcium sulfate whiskers, 15 parts of sodium carbonate and 10 parts of sodium metasilicate, and shear and stir at 600 r / min to mix evenly to obtain a concrete water-retaining and crack-resistant internal curing agent with a solid content of 24%.
[0038] Example 2
[0039] A concrete water-retaining and crack-resistant internal curing agent is prepared from the following raw materials in parts by weight: 31 parts of sodium metasilicate, 37 parts of calcium nitrate tetrahydrate, 45 parts of polyacrylic acid with a molecular weight of 2000, 32 parts of acrylamide, 22 parts of N,N-methylenebisacrylamide, 28 parts of 500-mesh calcium sulfate whiskers, 20 parts of sodium carbonate, 13 parts of hydroxypropyl cellulose ether, 1 part of Rongalite, 4 parts of hydrogen peroxide, 1.6 parts of mercaptoethanol, and 750 parts of deionized water.
[0040] The preparation method of the concrete water-retaining and crack-resistant internal curing agent includes the following steps:
[0041] S1: Add 32 parts of polyacrylic acid and 5 parts of acrylamide into a four-necked flask, add 200 parts of deionized water, and stir evenly at 25°C;
[0042] S2: Add 4 parts of hydrogen peroxide to the four-necked flask in step S1. After stirring evenly, simultaneously dropwise add material A composed of 22 parts of N,N-methylenebisacrylamide, 27 parts of acrylamide and 200 parts of deionized water, and material B composed of 1 part of sodium formaldehyde sulfoxylate and 1.6 parts of mercaptoethanol. The dropping time of material A is 80 min, and the dropping time of material B is 100 min. After the dropping is completed, stir and keep warm at 25 °C for 1.5 h.
[0043] S3: Add 300 parts of deionized water to the polyacrylic acid-acrylamide cross-linked product A obtained in step S2. Stir and shear at 500 r / min and heat up to 40 °C. Under the heat preservation condition, simultaneously dropwise add a 60% mass concentration calcium nitrate tetrahydrate solution containing 37 parts of calcium nitrate tetrahydrate and a 10% mass concentration sodium metasilicate solution containing 12 parts of sodium metasilicate. The dropping time is 1 h, and the heat preservation time is 3 h. After cooling to room temperature, add 13 parts of hydroxypropyl cellulose ether and stir to obtain reaction product B;
[0044] S4: Add the remaining deionized water to the reaction product B obtained in step S3 to dilute it, and add 28 parts of calcium sulfate whiskers, 20 parts of sodium carbonate and 19 parts of sodium metasilicate. Stir and shear at 600 r / min to mix evenly, and then the water retention and crack resistance internal curing agent for concrete with a solid content of 23% is obtained.
[0045] Example 3
[0046] A water retention and crack resistance internal curing agent for concrete is prepared from the following raw materials in parts by weight: 30 parts of sodium metasilicate, 36 parts of calcium nitrate tetrahydrate, 41 parts of polyacrylic acid with a molecular weight of 3000, 29 parts of acrylamide, 19 parts of N,N-methylenebisacrylamide, 22 parts of 600-mesh calcium sulfate whiskers, 16 parts of sodium carbonate, 12 parts of hydroxypropyl cellulose ether, 0.5 part of ascorbic acid, 3 parts of hydrogen peroxide, 1.2 parts of 3-mercaptopropionic acid, and 800 parts of deionized water.
[0047] The preparation method of the water retention and crack resistance internal curing agent for concrete includes the following steps:
[0048] S1: Add 41 parts of polyacrylic acid and 4 parts of acrylamide to a four-necked flask, add 200 parts of deionized water, and stir evenly at 25 °C;
[0049] S2: Add 3 parts of hydrogen peroxide to the four-necked flask in step S1. After stirring evenly, simultaneously dropwise add material A composed of 19 parts of N,N-methylenebisacrylamide, the remaining parts of acrylamide and 200 parts of deionized water, and material B composed of 0.5 part of ascorbic acid and 1.2 parts of 3-mercaptopropionic acid. The dropping time of material A is 80 min, and the dropping time of material B is 100 min. After the dropping is completed, stir and keep warm at 20 °C for 1 h.
[0050] S3: Add 200 parts of deionized water to the polyacrylic acid-acrylamide cross-linked product A obtained in step S2, shear and stir at 600 r / min and heat up to 40 °C. Under the insulation condition, simultaneously dropwise add a 60% mass concentration calcium nitrate tetrahydrate solution containing 36 parts of calcium nitrate tetrahydrate and a 10% mass concentration sodium metasilicate solution containing 11 parts of sodium metasilicate. The dropping time is 1 h and the insulation time is 3 h. After cooling to room temperature, add 12 parts of hydroxypropyl cellulose ether and stir to obtain reaction product B.
[0051] S4: Add the remaining parts of deionized water to dilute the reaction product B obtained in step S3, and add 22 parts of calcium sulfate whiskers, 16 parts of sodium carbonate and 19 parts of sodium metasilicate, and shear and stir at 600 r / min to mix evenly, thus obtaining a concrete water retention and crack resistance internal curing agent with a solid content of 20%.
[0052] Comparative Example 1
[0053] Others are the same as in Example 1, only sodium carbonate and calcium sulfate whiskers in the raw materials are omitted.
[0054] Comparative Example 2
[0055] A concrete water retention and crack resistance internal curing agent is prepared from the following raw materials in parts by weight: 10 parts of sodium metasilicate, 37 parts of polyacrylic acid, 26 parts of acrylamide, 11 parts of N,N-methylenebisacrylamide, 25 parts of 300-mesh calcium sulfate whiskers, 15 parts of sodium carbonate, 12 parts of hydroxypropyl cellulose ether, 0.7 part of ascorbic acid, 4 parts of hydrogen peroxide, 1.2 parts of 3-mercaptopropionic acid, and 550 parts of deionized water.
[0056] The preparation method of the concrete water retention and crack resistance internal curing agent includes the following steps:
[0057] S1: Add 37 parts of polyacrylic acid and 5 parts of acrylamide to a four-necked flask, add 200 parts of deionized water, and stir evenly at 20 °C;
[0058] S2: Add 4 parts of hydrogen peroxide to the four-necked flask in step S1, stir evenly, and simultaneously dropwise add material A composed of 11 parts of N,N-methylenebisacrylamide and 21 parts of acrylamide, and material B composed of 0.7 part of ascorbic acid and 1.2 parts of 3-mercaptopropionic acid. The dropping time of material A is 80 min, the dropping time of material B is 100 min. After the dropping is completed, stir and keep warm at 20 °C for 1 h to obtain polyacrylic acid-acrylamide cross-linked product A.
[0059] S4: Add the remaining parts of deionized water to dilute the polyacrylic acid-acrylamide cross-linked product A to a solid content of 30%, and add 25 parts of calcium sulfate whiskers, 15 parts of sodium carbonate and 10 parts of sodium metasilicate, and shear and stir at 600 r / min to mix evenly, thus obtaining the concrete water retention and crack resistance internal curing agent.
[0060] Test Example 1
[0061] For the samples of the concrete water retention and crack resistance internal curing agent prepared in each example and comparative example, C50 grade concrete was prepared using Conch P·O 42.5 grade cement and Class II fly ash. The concrete mix ratio was: cement 330 kg / m 3 , fly ash 75 kg / m 3 , sand 780 kg / m 3 , stone 1050 kg / m 3 , water 160 kg / m 3 . According to GB / T50081—2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete", the flexural and compressive strength tests of the concrete at 3d and 28d were carried out. The dosage of the internal curing agent was 1.5% of the binder. The obtained results are shown in Table 1;
[0062] Table 1 Influence of internal curing agent samples on the strength of C50 concrete at 3d / 28d
[0063]
[0064] Test Example 2
[0065] For the samples of the concrete water retention and crack resistance internal curing agent prepared in each example and comparative example, C30 grade concrete was prepared using Conch P·O 42.5 grade cement and Class II fly ash. The mix ratio of C30 grade concrete was: cement 260 kg / m 3 , fly ash 70 kg / m 3 , sand 930 kg / m 3 , stone 1000 kg / m 3 , water 160 kg / m 3 . According to GB / T50082—2009 "Standard Test Methods for Long-Term Performance and Durability of Ordinary Concrete", the plastic crack resistance performance test of the concrete was carried out. The dosage of the internal curing agent was 1.5% of the binder. The obtained results are shown in Table 2;
[0066] Table 2 Influence of internal curing agent samples on the durability of C30 concrete
[0067]
[0068] It can be seen from the above content that the concrete water retention and crack resistance internal curing agent provided by the present invention has good concrete curing function. After incorporation, the strength growth of the concrete is more excellent, and the cracking is significantly improved, and it can play an excellent concrete curing function in the environment with large temperature and humidity changes.
[0069] In Comparative Example 1, since sodium carbonate and calcium sulfate whiskers were omitted, the compactness of the concrete decreased, and at the same time, the promoting effect on hydration decreased, resulting in a certain decrease in the strength of the concrete. At the same time, the decrease in compactness led to a certain increase in the cracking degree of the concrete.
[0070] In Comparative Example 2, due to the lack of the synthesized calcium silicate hydrate particle solution, the hydration of the concrete lacked crystal nuclei, resulting in more loose hydration products. The strength development of the concrete was poor, and the loose hydration product structure led to a decrease in the anti-cracking effect.
[0071] The detailed description of a water-retaining and crack-resistant internal curing agent for concrete and its preparation method with reference to the examples is illustrative rather than restrictive. Several examples can be listed within the defined scope. Therefore, changes and modifications without departing from the general concept of the present invention should fall within the protection scope of the present invention.
Claims
1. A concrete water-retaining and anti-cracking internal curing agent, characterized in that: The high temperature difference concrete water-retaining and anti-cracking internal curing agent is prepared from the following raw materials in parts by weight: 22-37 parts of sodium metasilicate, 26-37 parts of calcium nitrate tetrahydrate, 30-47 parts of polyacrylic acid, 22-35 parts of acrylamide, 11-22 parts of N,N-methylenebisacrylamide, 21-30 parts of calcium sulfate whiskers, 14-22 parts of sodium carbonate, 7-18 parts of hydroxypropyl cellulose ether, 0.4-1.4 parts of reducing agent, 3-5 parts of oxidizing agent, 1.2-2 parts of chain transfer agent and 450-800 parts of deionized water.
2. The concrete water-retaining and anti-cracking internal curing agent according to claim 1, characterized in that: The molecular weight of the polyacrylic acid is 1000-3000.
3. The concrete water-retaining and anti-cracking internal curing agent according to claim 1, characterized in that: The particle size of the calcium sulfate whisker is 300-600 meshes.
4. The concrete water-retaining and anti-cracking internal curing agent according to claim 1, characterized in that: The reducing agent is ascorbic acid and bleaching agent.
5. The concrete water-retaining and anti-cracking internal curing agent according to claim 1, characterized in that: The oxidant is hydrogen peroxide or ammonium persulfate.
6. The concrete water-retaining and anti-cracking internal curing agent according to claim 1, characterized in that: The chain transfer agent is 3-mercaptopropionic acid, thioglycolic acid or mercaptoethanol.
7. The method for preparing the concrete water-retaining and anti-cracking internal curing agent according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1: First, stir and mix the formulated amount of polyacrylic acid, part of acrylamide and part of deionized water; S2: adding a formulated amount of oxidant to the mixed solution obtained in step S1, stirring evenly, and simultaneously adding dropwise material A consisting of N,N-methylenebisacrylamide, the remaining part of acrylamide and part of deionized water, and material B consisting of a reducing agent and a chain transfer agent, stirring and heat preservation after the addition is completed, and heat preservation is terminated to obtain a polyacrylic acid-acrylamide crosslinked product A; S3: Mix the polyacrylic acid-acrylamide cross-linked product A obtained in S2 with part of deionized water, stir and heat to 40-42° C., while maintaining the temperature, respectively add a tetrahydrate calcium nitrate solution and a sodium metasilicate solution dropwise, after the addition is complete, shear and stir to keep the temperature, cool to room temperature, add hydroxypropyl cellulose ether, and stir to obtain a reaction product B; S4: Add the remaining deionized water to the reaction product B to dilute it to a solid content of 20-40%, add sodium metasilicate, sodium carbonate and calcium sulfate whiskers, and mix them evenly by shearing and stirring to obtain a concrete water-retaining and anti-cracking internal curing agent.
8. The preparation method according to claim 7, characterized in that: In step S2, the dropwise addition time of material A is 60 to 100 min, and the dropwise addition time of material B is 80 to 120 min; the stirring and heat preservation time is 1±0.5 hours, and the temperature is maintained at 35 to 45°C.
9. The preparation method according to claim 7, characterized in that: In step S3, the calcium nitrate tetrahydrate solution and the sodium metasilicate solution are added dropwise for 80 to 80 minutes, and the shear stirring and heat preservation time is 2.5 to 3.5 hours.
10. A concrete, characterized in that: The concrete uses the concrete water-retaining and anti-cracking internal curing agent described in any one of claims 1 to 6.
